The Effect Of Discount Prices And Brand Image On Purchasing Decisions At Sports Station Banda Aceh - Hafizah, Nurul; Simangunsong, Sixson Roberto (SEAN Institute, 2024)
The problem in this research is, competition in the sports equipment industry is very strong. Like foreign brand companies and domestic companies, there is very strong competition. The problem that often influences consumer buying interest is the price factor.The research methodology used was quantitative and descriptive statistics. The research location was carried out at the Banda Aceh Sport Station. The variables in this research were discount prices as X1, brand image as X2 and the dependent variable was consumer purchasing decisions. Finding out if brand perception and discounted pricing have an impact on purchase decisions is the goal of this study. Thirteen responders made up the sample for this study. A questionnaire is used in this study's data collection procedure. Multiple Linear Regression Analysis is used in data analysis, and SPSS is used in data processing. With 0.04 <0.05 that brand image as variable > F Table (3.28) concurrently, the research results indicate that variable obtained T Count (3.135) > T Table (2.03) indicating that variable X2 has a significant effect on variable Y. that discount prices, brand image have a positive and significant effect on purchasing decisions.